Epidemiology and Control of Plant Diseases - Vitale, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is intended for a broad readership of phytopathologists. It includes different scientific contributions focused on many crucial aspects, such as the identification, characterization and rapid detection of plant diseases; predictive models and deep learning networks; and ecofriendly measures for disease management.